Pengaruh fermentasi dan penambahan gula pada organoleptik minuman kombucha bunga telang (Clitoria ternatea L.) - Rosyanne Kushargina; Inne Indraaryani Suryaalamsah; Rimbawan Rimbawan; Mira Dewi; Evy Damayanthi (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: Telang flower (Clitoria ternatea L.) is a plant with a high antioxidant content that can be used as a functional drink in tea. That can be fermented to produce Kombucha, which is rich in antioxidants and organic acids. Objectives: This study aimed to develop a formula for Telang flower kombucha and evaluate its organoleptic properties. Methods:  In a Completely Randomized Design (CRD) experiment, this research was conducted at the Food Processing Laboratory of the Bachelor of Nutrition Study Program, Faculty of Medicine and Health, Universitas Muhammadiyah Jakarta, from December to March 2023. Sugar was added to the fermentation process at varied concentrations (20%, 30%, and 40% w/v), while Telang flower tea was the control. Fifty-two untrained panellists participated in the hedonic quality evaluation, which included the evaluation of color, aroma, taste, and overall preference. The data were examined with the Kruskal-Wallis and Mann-Whitney tests.Results: The sensory evaluation demonstrated statistically significant (p=0,000) differences in color, aroma, and taste between the control and the three sugar-added treatments. Kombucha's color and aroma characteristics with 20% and 30% sugar additions were significantly different (p<0,05). However, the taste characteristics were not significantly different. The color of Kombucha with 20% and 40% sugar additions were not significantly different, nor was the aroma with 30% and 40% sugar additions. According to the hedonic test analysis results, panellists preferred adding 40% sugar over other treatments. Hence this formula was selected for this study. Conclusion: Telang flower kombucha's organoleptic properties are strongly influenced by the fermentation process and the amount of added sugar. Further research is needed to explore its bioactive compounds and health benefits.